Identification of High School Students' Science Process Skills: A Basis for Developing an Ecotourism-STEM Integrated Physics E-Module to Enhance Environmental Awareness - Abdul Kadir Alaydrus; Joni Rokhmat; A. Wahab Jufri; Gunawan; Aris Doyan; AA Sukarso (Journal of Educational Studies, 2026)
Science Process Skills (SPS) is an essential foundation in physics learning that requires the identification of students' initial profiles to ensure the development of appropriate teaching materials. However, this identification is often overlooked. Furthermore, the integration of the local environmental context and the STEM (Science, Technology, Engineering, and Mathematics) approach has the potential to be a relevant framework for improving scientific skills and environmental awareness. This study aims to identify students' SPS profiles as an empirical basis for developing an ecotourism-STEM-based physics e-module. The method used is a quantitative descriptive study with a survey technique. The research subjects consisted of 176 10th-grade students from SMAN 2 Mataram City and 38 students from SMAN 10 Mataram City who were selected purposively based on access to local ecotourism potential. The SPS test instrument was developed based on six main indicators, namely observation, classification, interpretation, prediction, experimental planning, and communication. Data were analyzed descriptively to map students' SPS profiles. The identification results show that students' SPS profiles are in the medium to low category with significant variability. The average SPS score at SMAN 2 Mataram City reached 38.52 (medium category) with a range of 3–68, while at SMAN 10 Mataram City the average score was 25.00 (low category) with a range of 3–75. The dimensions of experimental planning and data interpretation were the aspects with the lowest achievements, indicating that physics learning is still verification and procedural. This study concludes that identifying the SPS profile is a crucial stage in developing teaching materials that are adaptive to student needs. These findings form the basis for the development of an ecotourism-STEM integrated physics e-module designed to develop science process skills in a targeted manner while instilling environmental awareness through a contextual local context.